Antimicrobial Activity and Proposed Action Mechanism of Linalool Against Pseudomonas fluorescens - Guo, Fengyu; Chen, Qianping; Liang, Qiong; Zhang, Ming; Chen, Wenxue; Chen, Haiming; Yun, Yonghuan; Zhong, Qiuping; Chen, Weijun (Frontiers in Microbiology, 2021)
In this study, linalool, one of the principal components of essential oils, was used as an antibacterial agent to investigate the antibacterial activity and mechanism of linalool against Pseudomonas fluoresces. The reduction in membrane potential (MP), leakage of alkaline phosphatase (AKP) and the release of macromolecules, including DNA, RNA and protein confirmed that damage to cell wall membrane structure and leakage of cytoplasmic contents were due to the linalool treatment. Furthermore, the decrease of enzyme activity, including the succinate dehydrogenase (SDH), malate dehydrogenase (MDH), pyruvate kinase (PK), and ATPase indicated that linalool could lead to metabolic dysfunction and inhibit energy synthesis. In addition, the activity of respiratory chain dehydrogenase and metabolic activity of respiration indicated that linalool inhibits cellular respiration. These results revealed that linalool had strong antibacterial activity against P. fluorescens via membrane damage, bacterial metabolic and oxidative respiratory perturbations, interfering in cellular functions and even causing cell death. It was suggested that linalool may be a new potential source as food antiseptics in food systems.